PENGEMBANGAN INSTRUMEN PENILAIAN BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) PADA MATA PELAJARAN GAMBAR TEKNIK MESIN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X DESAIN GAMBAR MESIN DI SEKOLAH MENENGAH KEJURUAN NEGERI 12 KOTA BEKASI - Faizal, Haspi; Fahri Yasin, Moh.; Fikrianto, Misbah (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
This study aims to produce a valid and reliable HOTS-based mechanical engineering drawing assessment instrument and to measure the extent of the ability of vocational school students in the 4Cs (Communication, Collaborative, Critical Thinking and Creativity) in the subject of mechanical engineering drawing. The research methods are research and development (R&D), research and information gathering, planning, product draft development, field trials and final product revision. The distribution of point values from the results of the answers of class X DGM students on the questions that have been given is the average result of 21.17 out of 25 points, the middle or median value of the data is 21 out of 25 points and the range of values from the above data is 16-25 points. The results of this study show that the HOTS assessment instrument in the form of 30 questions consisting of 25 multiple choices and 5 descriptions, from the analysis of the question grid is (89.4%). From the aspect of material, language and construction for multiple-choice questions, namely (86.9%) and for description questions, namely (88.2%) were declared valid with the feasible category by experts. The results of the trial were 30 questions that were declared valid with a reliability value for multiple-choice questions of 0.796 and description questions of 0.657. In the differentiation test, multiple- choice question items were in the category of sufficient with the number of questions, namely 11 questions (44%) and for the good category, a total of 14 questions (56%) and the description questions were in the very good category with the number of questions, namely 5 questions (100%). The learning outcomes have increased, from an average score of 77.25 to 83.09.